Cachexia causes time‐dependent activation of the inflammasome in the liver - Rodrigo Xavier dasNeves; Alex S. Yamashita; Daniela M.R. Riccardi; Julia Köhn‐Gaone; Rodolfo G. Camargo; Nelson I. Neto; Daniela Caetano; Silvio P. Gomes; Felipe H. Santos; Joanna D.C.C. Lima; Miguel L. Batista Jr; José Cesar Rosa‐Neto; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2023)
Abstract Background Cachexia is a wasting syndrome associated with systemic inflammation and metabolic disruption. Detection of the early signs of the disease may contribute to the effective attenuation of associated symptoms. Despite playing a central role in the control of metabolism and inflammation, the liver has received little attention in cachexia. We previously described relevant disruption of metabolic pathways in the organ in an animal model of cachexia, and herein, we adopt the same model to investigate temporal onset of inflammation in the liver. The aim was thus to study inflammation in rodent liver in the well‐characterized cachexia model of Walker 256 carcinosarcoma and, in addition, to describe inflammatory alterations in the liver of one cachectic colon cancer patient, as compared to one control and one weight‐stable cancer patient. Methods Colon cancer patients (one weight stable [WSC] and one cachectic [CC]) and one patient undergoing surgery for cholelithiasis (control, n = 1) were enrolled in the study, after obtainment of fully informed consent. Eight‐week‐old male rats were subcutaneously inoculated with a Walker 256 carcinosarcoma cell suspension (2 × 107 cells in 1.0 mL; tumour‐bearing [T]; or phosphate‐buffered saline—controls [C]). The liver was excised on Days 0 (n = 5), 7 (n = 5) and 14 (n = 5) after tumour cell injection. Results In rodent cachexia, we found progressively higher numbers of CD68+ myeloid cells in the liver along cancer‐cachexia development. Similar findings are described for CC, whose liver showed infiltration of the same cell type, compared with both WSC and control patient organs. In advanced rodent cachexia, hepatic phosphorylated c‐Jun N‐terminal kinase protein content and the inflammasome pathway protein expression were increased in relation to baseline (P < 0.05). These changes were accompanied by augmented expression of the active interleukin‐1β (IL‐1β) form (P < 0.05 for both circulating and hepatic content). Conclusions The results show that cancer cachexia is associated with an increase in the number of myeloid cells in rodent and human liver and with modulation of hepatic inflammasome pathway. The latter contributes to the aggravation of systemic inflammation, through increased release of IL‐1β.